Application of Peer Group Support with the Health Promotion Model Approach in Increasing Perceived Benefit Of Action and Perceived Self Efficacy - Khamida - Khamida; Syiddatul Budury; Siti - Nurjanah; Nur - Ainiyah; Chilyatiz - Zahroh (Alma Ata University Press, 2020)
There are problem related to students health behavior in Islamic boarding school, such as they do not washing their hand before they have their meals, hanging wet clothes in their room, and they do not really care to the toilet hygiene. The aims of this research was to knowing the effect of peer group support to perceived benefit of action and perceived self efficacy by applying students lifestyle management using health promotion model approach. The design was quasy experimental, pre post test control group the population were students who stayed in Islamic boarding school in An Najiyah, As Syafiiyah and Al Jihad Surabaya, and the total sample was 150 student, 75 in control group, 75 in intervention group, the sample taken by simple random sampling. In intervention group they’ve got health education and peer group support while the control only got health education by giving a student lifestyle management module. The independent variable was peer group support and dependent variable were perceived benefit of action and perceived self efficacy. The data taken by questionnaire and was analyzed by Wilcoxon signed test and Mann Whitney test. The result showed that after the treatment, students in intervention group have positive perceive benefit of action was 92% and 100 % have high perceived self efficacy, meanwhile in control group there were 72% students who have negative perceived benefit of action and 60% have low perceived self efficacy. It means that peer group support could change the students perception and increasing self efficacy to set a going lifestyle management based on health promotion model approach.